Aryl Hydrocarbon Receptor Facilitates DNA Strand Breaks and 8-Oxo-2′-deoxyguanosine Formation by the Aldo-Keto Reductase Product Benzo[a]pyrene-7,8-dione - Park, Jong-Heum (American Society for Biochemistry and Molecular Biology, 2009)
Polycyclic aromatic hydrocarbon (PAH) o-quinones produced by aldo-keto reductases are ligands for the aryl hydrocarbon receptor (AhR) (Burczynski, M. E., and Penning, T. M. (2000) Cancer Res. 60, 908–915). They induce oxidative DNA lesions (reactive oxygen species-mediated DNA strand breaks and 8-oxo-7,8-dihydro-2′-deoxyguanosine (8-oxo-dGuo) formation) in human lung cells. We tested whether the AhR enhances PAH o-quinone-mediated oxidative DNA damage by translocating these ligands to the nucleus. Using the single cell gel electrophoresis (comet) assay to detect DNA strand breaks in murine hepatoma Hepa1c1c7 cells and its AhR- and aryl hydrocarbon receptor nuclear translocator-deficient variants, benzo[a]pyrene-7,8-dione (B[a]P-7,8-dione) produced fewer DNA strand breaks in AhR-deficient cells compared with aryl hydrocarbon receptor nuclear translocator-deficient and wild type Hepa1c1c7 cells. Decreased DNA strand breaks were also observed in human bronchoalveolar H358 cells in which the AhR was silenced by siRNA. The antioxidant α-tocopherol and the iron chelator/antioxidant desferal decreased the formation of B[a]P-7,8-dione-mediated DNA strand breaks indicating that they were reactive oxygen species-dependent. By coupling the comet assay to 8-oxoguanine glycosylase (hOGG1), which excises 8-oxo-Gua, strand breaks dependent upon this lesion were measured. hOGG1 treatment produced more DNA single strand breaks in B[a]P-7,8-dione-treated Hepa cells and H358 cells than in its absence. The levels of hOGG1-dependent DNA strand breaks mediated by B[a]P-7,8-dione were lower in AhR-deficient Hepa and AhR knockdown H358 cells. The AhR antagonist α-naphthoflavone also attenuated B[a]P-7,8-dione-mediated DNA strand breaks. The decrease in 8-oxo-dGuo levels in AhR-deficient Hepa cells and AhR knockdown H358 cells was validated by immunoaffinity capture stable isotope dilution ([(15)N(5)]8-oxo-dGuo) liquid chromatography-electrospray ionization/multiple reaction monitoring/mass spectrometry. We conclude that the AhR shuttles PAH o-quinone genotoxins to the nucleus and enhances oxidative DNA damage.